ROLE OF MRI IN THE DIAGNOSIS OF URETERAL OBSTRUCTION IN CANCER PATIENTS (LITERATURE REVIEW) - Y. E. Suraeva (Сибирский онкологический журнал, 2017)
Complications related to the impairment of the urinary flow along the urinary tract in cancer patients are the important aspect in determining the treatment strategies for these patients. The level of ureteral obstruction is an especially important factor in diagnosis of this pathology. The excretory urography and computed tomography are effective tools in determining the level of ureteral obstruction, but their capabilities in identifying the causes of urodynamic disturbances in cancer patients are limited by the evaluation of the presence/absence of concrements. The magnetic resonance imaging (MRI) is considered as the safe alternative method. It is characterized by high tissue specificity and is able to detect not only the level of ureteral obstruction, but also the cause of its occurrence. It is especially important to note that even using contrast enhancement, MRI is a safe diagnostic tool, emitting no ionizing radiation. The MRI-based accurate diagnostic algorithm for this cohort of patients decreases the number of diagnostic procedures, especially the invasive ones. It provides opportunity to start etiological treatment earlier, thus safeguarding a kidney function.